Substantial cell apoptosis provoked by naked PAMAM dendrimers in HER2-positive human breast cancer via JNK and ERK1/ERK2 signalling pathways - Hadeel, Kheraldine (2021)
HER2-positive breast cancer is one of its most challenging subtypes, forming around 15–25% of the total cases. It is characterized by aggressive behavior and treatment resistance. On the other hand, poly (amidoamine) (PAMAM) dendrimers are widely used in drug delivery systems and gene transfection as carriers. PAMAMs can modulate gene expression and interfere with transactivation of the human epidermal growth factor receptor family members (HER1-4). Nevertheless, the outcome of PAMAMs on HER2-positive breast cancer remains unknown. Thus, in this study, we investigated the anti-cancer effects of different generations of PAMAM dendrimers (G4 and G6) and the outcome of their surface chemistries (cationic, neutral, and anionic) on HER2-positive breast cancer cell lines, SKBR3 and ZR75. Our data showed that PAMAM dendrimers, mainly cationic types, significantly reduce cell viability in a dose-dependent manner. More significantly, PAMAMs induce substantial cell apoptosis, accompanied by the up-regulation of apoptotic markers (Bax, Caspases-3, 8 and 9) in addition to down-regulation of Bcl-2. Moreover, our data pointed out that cationic PAMAMs inhibit colony formation compared to controls and other types of PAMAMs. The molecular pathway analysis of PAMAM exposed cells revealed that PAMAMs enhance JNK1/2/3 expression while blocking ERK1/2, in addition to EGFR1 (HER1) and HER2 activities, which could be the major molecular pathway behind these events. These observed effects were comparable to lapatinib treatment, a clinically used inhibitor of HER1 and 2 receptors phosphorylation. Our findings implicate that PAMAMs may possess important therapeutic effects against HER2-positive breast cancer via JNK1/2/3, ERK1/2, and HER1/2 signalling pathways.